AN EXAMINATION ON ONLINE LIFE INSURANCE PRICING: Differences between retaiers and financial services companies - WANG, FANG (2006)
The rapid growth of the Internet has promoted the online purchase of life insurance. This dissertation attempt to examine the online quoting price of term life insurance from different insurance providers which include specialised insurance companies: Norwich Union, broker: The AA, banks: Halifax and Nationwide and supermarket retailers: Sainsburys and ASDA. The prices of term life insurance with Critical Illness Cover from three companies are also examined, which include The AA, Halifax and Norwich Union. The result indicates that the lowest price is offered by the broker (The AA), followed by supermarkets (ASDA and Sainsburys), then followed the specialised insurance company (Norwich Union), then the highest prices come from banks (Nationwide and Halifax). However, the elasticity of piece with respect to age is higher for supermarket than for banks. The AA offers the most expensive term life insurance with Critical Illness Cover among three companies. At the same time, there is relatively low price dispersion across the Internet.